Perancangan Film Pendek Etika Mahasiswa Terhadap Dosen Program Studi Teknik Informatika Universitas PGRI Madiun - Yoga Prisma Yuda; Muh Nur Luthfi Azis (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
The use of multimedia has been used in various purposes at this time. Began to be used as an entertainment media, advertising, business and also education. The short movie is a part of multimedia. Using a short movie in educational media is very popular today. In making a short movie, it is necessary to design story concepts and techniques. In " Perancangan Film Pendek Etika Mahasiswa Terhadap Dosen Program Studi Teknik Informatika Universtas PGRI Madiun" aims to provide education about student ethics towards lecturers in the Universitas PGRI Madiun campus environment, especially in the Informatics Engineering Study Program.